The error analysis of the measurement of permittivity of crude oil with the use of interdigital capacitor sensor - Sylwia Przywska; Melania Suweni Muntini (Jurnal Fisika dan Aplikasinya, 2016)
Abstract-This paper presents the error analysis of the measurement of permittivity of crude oil with the use of a sensor designed and fabricated in our laboratory. The sensor is a interdigital capacitor sensor fabricated with the use of Printed Circuit Board (PCB) technology. This paper also presents the methodology of making the measurement of permittivity of crude oil sample. The discussion of the data obtained during the experiment is presented as well.